2009
DOI: 10.1080/08860220802599163
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Immunosuppressive Drugs on Platelet Aggregation and Soluble P-Selectin Levels in Renal Transplant Patients

Abstract: Background/aim. Post-transplant cardiovascular events are associated with increased morbidity and mortality after renal transplantation. Though renal transplantation eliminates cardiovascular disease risk factors by restoring renal function, it introduces new cardiovascular risks derived partly from immunosuppressive medications. In this study, to assess the effects of various immunosuppressive drugs on platelet function of renal transplant patients, we measured soluble P selectin levels (sP-selectin) and perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…Because both azathioprine and mycophenolate mofetil have similar mechanisms of action, it was expected that these medications would have similar results. The results of our study are similar to previous studies performed in humans that did not identify a significant change in measures of hemostasis during treatment with azathioprine or mycophenolate mofetil …”
Section: Discussionsupporting
confidence: 91%
“…Because both azathioprine and mycophenolate mofetil have similar mechanisms of action, it was expected that these medications would have similar results. The results of our study are similar to previous studies performed in humans that did not identify a significant change in measures of hemostasis during treatment with azathioprine or mycophenolate mofetil …”
Section: Discussionsupporting
confidence: 91%
“…This is due partly to the perception that cyclosporine has a more favorable adverse effect profile when compared with other immunosuppressive agents . Recent studies in humans, however, have shown that cyclosporine can alter the platelet plasma membrane, increase the thrombogenic properties of platelets, and accelerate thrombin generation . Approximately 50% of dogs with IMHA have been shown to be in a hypercoagulable state, predisposing these patients to complications such as pulmonary thromboembolism (PTE) .…”
mentioning
confidence: 99%
“…The exact mechanisms of PTE are not completely understood, but it is hypothesized that predisposing prothrombotic conditions involves both blood platelets and the clotting system . Results of several studies in humans have suggested that cyclosporine may enhance platelet reactivity, a finding that necessitates a better understanding of how canine platelets interact with this medication, and if drug administration is a potential risk factor for PTE. A recent pilot study performed in our laboratory using a small number of dogs found increased platelet P‐selectin expression (an adhesion protein with procoagulant and proinflammatory properties) after administration of cyclosporine .…”
mentioning
confidence: 99%
“…2). It has been shown that soluble Pselectin, responsible of platelet adhesion, is enhanced in patients treated with CsA, compared to FK506 and control platelets [111]. Surface expression of P-selectin is enhanced in resting platelets of renal transplanted patients, and it was further enhanced after stimulation with thrombin in patients treated with CsA and FK506 [109].…”
Section: Immunophilin Inhibitors Alter Platelets Secretion and Aggregmentioning
confidence: 98%
“…The role of immunophilins and cyclophilins in platelet activity and aggregation still remains controversial, with studies reporting thrombocytopenia [99][100][101][102][103][104][105][106], platelet hyperactivity [108][109][110] or platelet activity inhibition [111][112] in patients. This controversy might be attributed to the number of intracellular pathways altered by these inhibitors (See Fig.…”
Section: Immunophilin Inhibitors Alter Platelets Secretion and Aggregmentioning
confidence: 99%